2021
DOI: 10.1094/mpmi-04-21-0090-a
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence Data of Four Burkholderia glumae Strains Isolated from Rice Fields in the United States

Abstract: Bacterial panicle blight caused by Burkholderia glumae is a major disease in rice production worldwide. Currently, only a few whole-genome sequences of B. glumae strains isolated in the U.S. are available. Here, we report the complete genome sequence of four B. glumae strains, including three virulent strains (336gr-1, 411gr-6, and 957856-41-c) and the non-pathogenic strain B. glumae 257sh-1, which were isolated from rice fields in Louisiana (336gr-1, 957856-41-c, and 257sh-1) and Arkansas (411gr-6). The whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Once detected and characterized using the above approaches, six strains (60BGCRMSO1-5, 60BGCRMSO3-5, 60BGCRMSO3-9, 60BGCRMSO3-11, 60BGCRPA10-1, and 60BGCRWC8-5) were selected and subjected to whole-genome sequencing, characterization, and phylogenetic analysis. The genome characteristics of the sequenced strains were consistent with the previously sequenced strains of this pathogen (e.g., [20,21,32,33]), with a high level of completeness (Table 2). The toxoflavin gene cluster of the six genomes was identified and compared with the other publicly available B. glumae genomes.…”
Section: Discussionsupporting
confidence: 77%
“…Once detected and characterized using the above approaches, six strains (60BGCRMSO1-5, 60BGCRMSO3-5, 60BGCRMSO3-9, 60BGCRMSO3-11, 60BGCRPA10-1, and 60BGCRWC8-5) were selected and subjected to whole-genome sequencing, characterization, and phylogenetic analysis. The genome characteristics of the sequenced strains were consistent with the previously sequenced strains of this pathogen (e.g., [20,21,32,33]), with a high level of completeness (Table 2). The toxoflavin gene cluster of the six genomes was identified and compared with the other publicly available B. glumae genomes.…”
Section: Discussionsupporting
confidence: 77%
“…The whole genome sequence information of the B. glumae strains 336gr-1 (virulent, non-pigmenting), 257sh-1 (avirulent, pigmenting), and 411gr-6 (hyper-virulent, pigmenting) was announced previously [16]. Their phenotypic traits are presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In that study, we identified hypervirulent, virulent, hypo-virulent, and naturally avirulent strains. Further, we sequenced the whole genomes of four strains representing different phenotypes in virulence and pigment production on CPG agar medium: 336gr-1 (virulent and non-pigment-producing), 411gr-6 (highly virulent and pigment-producing), 957856-41-c (hypo-virulent and non-pigment-producing), and 257sh-1 (avirulent and pigment-producing) [16].…”
Section: Introductionmentioning
confidence: 99%
“…We sprayed with the bacterial suspension of B. glumae when panicles were emerging (20 to 30% emerged) from the boot at the booting stage. Empty seeds were calculated by cutting four rice ears from both processed and unprocessed plants (at the heading stage) to evaluate the empty seed rate [41]. The leaves of adult plants (2 months old) were inoculated with bacterial suspensions of Xoc.…”
Section: Pathogenicity Tests Of Parents and Offspringmentioning
confidence: 99%